In Memoriam: Prof. Dr. Božidar Ćurčić (1946-2015) - Dimitrijević, Rajko (Macedonian Journal of Ecology and Environment, 2016)
Prof. Dr. Božidar Ćurčić was born on 3rd July in Belgrade, where he graduated in 1969 at the Faculty of Science (Biology). The same year he was posted in the Institute of Zoology, Faculty of Science, University of Belgrade, where he spent his whole university career. During all these years he successfully conducted his fruitful scientific research and lectured at both graduate and postgraduate levels.